Non-Pharmacological Therapy To Control Blood Pressure in Patients with Hypertension: Literature Review - Anam Muhtarul (Program Studi Ilmu Keperawatan FIKES UNIBBA, 2024)
Hypertension has a significant negative impact on cardiovascular morbidity and mortality. It is associated with many cardiovascular complications and is responsible for 10.4 million deaths and 208.1 million life expectancy-adjusted disabilities. Target blood pressure levels and blood pressure control remain poor despite the availability of numerous pharmacological therapy options. When anti-hypertensive medicine cannot achieve blood pressure targets due to various factors, other alternative treatments are needed so that optimal patient health status can be achieved, one of which is non-pharmacological therapy. The purpose of this study was to identify non-pharmacological therapies to control blood pressure in patients with hypertension. The method used in this study is literature review. The study results of 8 articles obtained non-pharmacological therapies used are low sodium diet, lifestyle modification (conventionally and with the help of applications), reflexology, and exercise. Out of the available non-pharmacological therapies, reflexology was found to have the most significant blood pressure lowering effect in patients with hypertension. This suggests that non-pharmacological therapies are effective in controlling the BP of hypertensive patients.